Information Needs of Rythu Mitra Group Members of Andhra Pradesh - Manti Venkataramulu; Ram Bahal; Premalata Singh; Baldeo Singh (Journal of Agricultural Extension Management, 2014)
This study was conducted on the information needs of Rythu Mitra Group members in Warangal and Guntur districts of Andhra Pradesh. Results reveal that information needs of farmer respondents on personal and family health and education assume great importance. Among the agriculture and allied sectors, respondents needed information on soil conservation and forest management, water resources sector, agriculture and horticulture, animal husbandry, sericulture, fisheries, etc. Extension workers need to focus on the information needs of farmers, especially relating to agriculture and horticulture